ANALISIS SISTEM PELAYANAN ADMINISTRASI KEPENDUDUKAN BERBASIS APLIKASI E-OPEN DI KELURAHAN PEJUANG KOTA BEKASI - Irma Aini Anriani; Erene Gernaria Sihombing (LPPM Universitas Putera Batam, 2022)
E-Open application user satisfaction is a level where the needs, desires and expectations of E-Open application users can be met which results in people using E-Open applications for administrative purposes in the village. The warrior village is one of the villages in the Medan Satria sub-district, Bekasi. There are many things that must be considered in using the E-Open application, namely by providing something that is in accordance with the needs of the warrior village community. Based on these problems, the researchers found that the suitability of the E-Open application with administrative activities in the urban village would make it easier to provide services to the warrior village. Sources of data were obtained from distributing questionnaires to people who had used the E-Open application in the warrior village to 101 people. The attributes used as parameters for evaluating the satisfaction of E-Open application users include: gender, age, occupation, E-Open Usability Level, E-Open Application Image, E-Open Service Quality, E-Open User Quality. The results of processing the C4.5 method using a decision tree after determining the Entropy and Gain. The model that has been formed is tested for accuracy by entering the initial data. For the value of user satisfaction of the E-Open application.